2018
DOI: 10.1007/s11665-018-3276-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Thermomechanical Processes on the Microstructure, Texture, and Mechanical Properties of API 5L X70 Steel

Abstract: A commercial API 5L X70 steel plate was subjected to different thermomechanical processes to propose a novel thermomechanical rolling path to achieve improved mechanical properties. Scanning electron microscopy, electron backscatter diffraction, and x-ray texture analysis were employed for microstructural characterization. The results showed that strain-free recrystallized {001} ferrite grains that developed at higher rolling temperature could not meet the American Petroleum Institute (API) requirements. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…It is clearly observed that the application of accelerated cooling just after finish rolling is very effective in producing smaller grained (3.9 -4.1 m µ ) microstructures as compared to the ambient cooling (5.2 -6.4 m µ ). The average grain size values determined in this work were inline with the values reported in the literature [25,26]. For example, in a similar study Masumi et.…”
Section: Microstructural Examinationssupporting
confidence: 90%
See 1 more Smart Citation
“…It is clearly observed that the application of accelerated cooling just after finish rolling is very effective in producing smaller grained (3.9 -4.1 m µ ) microstructures as compared to the ambient cooling (5.2 -6.4 m µ ). The average grain size values determined in this work were inline with the values reported in the literature [25,26]. For example, in a similar study Masumi et.…”
Section: Microstructural Examinationssupporting
confidence: 90%
“…For example, in a similar study Masumi et. al found the average ferrite grain size to be around 5-6 m µ without accelerated cooling [25]…”
Section: Microstructural Examinationsmentioning
confidence: 99%
“…The current view from some investigators is that the structure units affecting toughness are grains with grain boundary misorientation angles greater than 15° in acicular ferrite pipeline steels. In other words, the high-angle grain boundaries (HAGB) with grain boundary misorientation angles greater than 15° are the effective grains, and cracks will be arrested and then deflected by a large angle when encountering HAGB in the process of crack propagation [12,17,18]. However, a large number of experiments show that cracks can also pass straight through HAGB between grains (as shown in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [36] indicated that the recrystallisation textures by cold rolling and annealing mainly consisted of Brass orientation {110}〈112〉 and partial Goss orientation {110}〈100〉. Some studies have shown that the {110} orientations provided an outstanding combination of tensile strength and ductility [37,38]. As shown in Figure 4(d), the average grain size of the NG/UFG sample was calculated to be 335 nm from the grain size distribution histogram.…”
Section: Resultsmentioning
confidence: 99%